THU0705 Occurrence of ankylosing spondylitis (AS) among relatives of probands with radiographic as and non-radiographic as/axial spondyloarthritis (SPA). (12th June 2018) - Van Der Linden, S.; Villiger, P.; Baumberger, H.; Brown, M.; Boonen, A.; Khan, M.A.
Abstract : Background: The occurrence of AS in families as it relates to the presence or absence of HLA-B27 and radiographic sacroiliitis is not well-known. Objectives: To assess among relatives the occurrence of AS and its association with HLA-B27 and presence of sacroiliitis among AS probands. AS is broader than just radiographic (classical) AS by modified New York criteria (mNY). We asked whether the likelihood of having a relative with classical AS is comparable for probands with radiographic AS by mNY criteria, and probands with non-radiographic AS/axSpA. Methods: Re-analysis of the 1985–86 Swiss AS Family Study: 1178 subjects (363 clinically defined AS probands, 806 first-degree relatives, and 9 spouses) had participated. The AS patients were members of the Swiss AS patient society. The invited and consenting participants underwent physical exam of the spine and joints, completed questionnaires dealing with musculoskeletal problems, had pelvic radiographs taken, and provided blood samples for HLA-A, B, C typing. Radiographs were blindly read twice by each of up to 4 experienced readers. They scored sacroiliac joints according to NY criteria for sacroiliitis (bilateral grade ≥2 or unilateral grade ≥3). The study had been approved by the ethical committee of the University of Bern, Switzerland. Results: Among 358 AS probands, 308 (86%) were HLA-B27(+) and 50 (14%) lacked this gene. The radiographic NY criteria were met by 81% of the 308 HLA-B27(+) probands versus only 44% of the 50 HLA-B27(-) probands. AS, as defined by NY criteria, was observed only among relatives of HLA-B27(+) probands; and all 14 of these relatives were also HLA-B27(+). Note: The probands in 12 of these 14 cases met the NY criteria, while 2 did not. Two of 59 HLA-B27(+) relatives from AS probands not-fulfilling the mNY criteria met the NY criteria, compared with 12 of 245 HLA-B27(+) relatives from AS probands fulfilling the mNY criteria (p=0.62). Interestingly, inflammatory back pain (by Calin criteria) occurred among 46 of 286 (16.1%) HLA-B27(+) relatives of HLA-B27(+) probands, but in only 27 of 272 (9.9%) HLA-B27(-) relatives of HLA-B27(+) probands (p=0.031). Conclusions: AS among relatives was only observed in families of HLA-B27(+) AS/axSpA probands. The risk for HLA-B27(+) relatives to develop AS by NY criteria seems not to be influenced by the presence of sacroiliitis in the HLA-B27(+) AS/axSpA probands. HLA-B27(+) relatives who do not show radiographic sacroiliitis are at higher risk to demonstrate symptoms of non-radiological AS/axSpA as they seem more prone to have inflammatory back pain. Reference: [1] Khan MA, van der Linden SM, Kushner I, Valkenburg HA, Cats A. Spondylitic disease without radiologic evidence of sacroiliitis in relatives of HLA-B27 positive ankylosing spondylitis patients. Arthritis Rheum1985;28(1):40–3. Disclosure of Interest: None declared